Pulmonary Complications and Critical Care in Cancer Patients - Darmi, MD, Dr. B. A. (International Journal of Innovative Research in Medical Science, 2018)
Cancer refers to the condition where abnormal proliferation of cells occurs overriding the natural check of cell death.[1] As a normal physiological process, all cells of our body are programmed to die - called as apoptosis.[2] In cancer, the balance between cell proliferation and cell death is disrupted, resulting in uncontrolled division of cells.[3] Hence, apoptosis is an anti-cancer defense of body. In other words, carcinogenesis involves sequential genetic change that transforms normal cells to malignant cells. The cancer cells interfere with normal physiological functions and kill by invading various body organs vital for living. Cancer is a second leading cause of death worldwide, estimated to kill 9.6 million people in 2018.[4] Approximately, every sixth death is caused by cancer.[4] Globally, most common cancers are lung, breast, colorectal, prostate, skin and stomach cancers.